Legal Remedies for Default Against Default Decisions in Divorce Lawsuits (Case Study of Indramayu Religious Court Decision Class IA Number 731/Pdt.G2024/PA.IM) - Atoillah, Atoillah; Mansur, Mansur (Universitas Wiralodra, 2025)
Legal Efforts of Verzet (resistance) are a form of resistance to the Verzet decision that has been issued by the Panel of Judges at the first instance Court (Religious Court), which is filed by the Defendant . In Verzet cases , unwanted problems usually occur, so the party who feels aggrieved can file a Verzet resistance . The issuance of the Verzet decision is the impact of the Village official or third party who immediately does not submit a release of the Court's summons so that in the process of examining a divorce case at the Religious Court, Verzet Decisions often occur so that this situation becomes a problem that becomes a common enemy for both the party that issued the decision product, namely the Indramayu Religious Court and the community seeking justice. So it is not surprising that the three defendants made resistance efforts (verzet) and even criminal reporting efforts for perpetrators who removed and did not submit the release of the summons to the defendant and even to the plaintiff. The research method used in this study is normative legal research. Qualitative research such as using non-numerical data, such as interviews, observations, and text analysis, to understand the social and cultural phenomena that occur. With the problem of what is the legal basis for the default decision of the Indramayu Religious Court Number 731/Pdt.G/2024/PA.IM. to provide a sense of justice and what legal efforts are made in cases with default decisions against the defendant based on the decision of the religious court Number 731/Pdt.G/2024/PA.IM . This study examines two important aspects in Indonesian civil procedural law related to default decisions. First, a comprehensive review of the default decision process which is a decision that is issued without the presence of the defendant even though he has been properly summoned, including the procedure for a valid summons, examination of the completeness of the lawsuit, the judge's considerations, and the defendant's right to file a default legal remedy. Second, an analysis of the considerations of the Panel of Judges in deciding the case of objection to the default decision in the case of divorce lawsuit Number: 731/Pdt.G/2024/PA.IM, with an emphasis on formal and material aspects, including the validity of the summons procedure, the absence of the defendant, the validity of the submission of the default, and the substance of the objection filed by the defendant. This study aims to analyze the suitability between the theory of civil procedural law and judicial practice in the specific context of divorce lawsuit cases in the Religious Court.